PENGARUH PENERAPAN EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN (Study pada Coffee Toffee Malang). - Ariyanto, Maria Marcellina (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the magnitude of experiential marketing effect on customer loyalty of Coffee Toffee Malang. This is an explanatory research. The sampling technique used is non-probability sample with purposive sampling method. The sample in this study comprised 240 respondents who are the customers of Coffee Toffee Malang. Data used in this study are primary data and secondary data. Data collection instrument is questionnaire measured by using Likert scale. This study uses multiple linear regression model to test the hypothesis. Hypothesis test was run both in simultaneous and partial tests, as well as dominant test. The results showed that Experiential Marketing consisting of five variables, namely sense, feel, think, act, and relate, is able to simultaneously increase customer loyalty of Coffee Toffee Malang. Greater sense will increase customer loyalty of Coffee Toffee Malang. The same is true for the other independent variables. If feel, think, act, and relate increase it will result in greater customer loyalty of Coffee Toffee Malang. Feel variable if it gets improved will contribute most to the increase of customer loyalty of Coffee Toffee Malang compared with the other variables.Keywords: Experiential Marketing, Sense, Feel, Think, Act, Relate, Customer Loyalty